Role of Papain-Like Cysteine Proteases in Plant Development - Liu, Huijuan; Hu, Menghui; Wang, Qi; Cheng, Lin; Zhang, Zaibao (Frontiers in Plant Science, 2018)
Papain-like cysteine proteases (PLCP) are prominent peptidases found in most living organisms. In plants, PLCPs were divided into nine subgroups based on functional and structural characterization. They are key enzymes in protein proteolysis and involved in numerous physiological processes. In this paper, we reviewed the updated achievements of physiological roles of plant PLCPs in germination, development, senescence, immunity, and stress responses.